2001
DOI: 10.2134/agronj2001.932299x
|View full text |Cite
|
Sign up to set email alerts
|

Grass and Legume Cover Crop Effects on Dry Matter and Nitrogen Accumulation

Abstract: concentration of the cover crop mixture through biological N fixation and minimizing the potential for short-Careful cover crop management during the spring growth period term N immobilization (Ranells and Wagger, 1997). may allow farmers to maximize dry matter (DM) yield and N accumulation for the subsequent crop. A 2-yr study was conducted to deter-In cool northern climates such as Ontario (Tollenaar mine the effect of grass and legume cover crops on spring DM produc- et al., 1993), Washington (Kuo et al., 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 24 publications
12
50
1
3
Order By: Relevance
“…In both 2007 and 2008, rye total dry matter yields were lower than those reported in literature (Vaughan and Evanylo, 1999;Odhiambo and Bomke, 2001). In Maryland, Clark et al (1994) reported maximum winter rye biomass as cover crop in the range of 6400 and 7100 kg ha −1 .…”
Section: Cover Crop Yield and Nitrogen Utilizationmentioning
confidence: 54%
“…In both 2007 and 2008, rye total dry matter yields were lower than those reported in literature (Vaughan and Evanylo, 1999;Odhiambo and Bomke, 2001). In Maryland, Clark et al (1994) reported maximum winter rye biomass as cover crop in the range of 6400 and 7100 kg ha −1 .…”
Section: Cover Crop Yield and Nitrogen Utilizationmentioning
confidence: 54%
“…Strock et al (2004) applied 134 kg N/ha of Urea to corn and measured southwestern Minnesota winter rye cover crop biomass of 2.7 Mg/ha in spring of 1999 and 1.0 Mg/ha in spring of 2000 with nitrogen concentration of 2.5% and 2.7%, respectively. Also, Odhiambo and Bomke (2001) and Weinert et al (2002) found N concentration in rye and wheat cover crop of 2.9% to 2.2% for biomass of 2.1 to 3.8 Mg/ha. Therefore, the above ground biomass critical and/or minimum N concentration limits used in APSIM may be too low considering that the terminal crop stage for the wheat was floral initiation.…”
Section: Apsim Predicted Winter Wheat Cover Crop Effectmentioning
confidence: 97%
“…Winter cover crops minimize soil nitrate before and after the growing season, when it is most subject to leaching (Eigenberg et al, 2002). Winter wheat and rye have been used as cover crops and the biomass nitrogen contents of the two crops are often similar (Odhiambo and Bomke, 2001;Weinert et al, 2002). In general, management strategies to reduce nitrate loss have only been tested over a few years and limited environmental and management conditions, therefore, quantifying the effects under the variety of expected conditions is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops have been shown to influence nitrogen cycling [11][12][13], reduce soil erosion, water run-off and soil losses during intense rainfall events [14][15][16], increase soil organic matter and soil fertility [17][18][19][20][21], suppress weed growth [22][23][24][25], improve soil structure and water holding capacity [26,27], provide suitable habitat for beneficial predator insects and act as non-host crops for nematodes and other pests in the rotation [28]. Legume cover crops also fix their own nitrogen and contribute to the nitrogen requirements of the subsequent crops [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%